The nutritional value study of acidophilic-whey ice cream - Polishchuk, Galyna; Osmak (Fedchenko), Tetiana; Bass, Oksana; Mykhalevych, Artur (My University, 2021)
The dietary structure of most people is extremely inconsistent with modern principles of rational nutrition and practical dietetics. Consumer rations often have an excess of foods with a high carbohydrate content and very little of the main sources of complete protein, dietary fiber and micronutrients. The scientific studies results of the actual nutritional status of the population in different regions indicate that the nutritional status of the child and adult population is seriously impaired. The reason for such a violation is the deficiency of complete (animal) proteins, polyunsaturated fatty acids, vitamins, macro- and microelements, as well as dietary fiber. Conversely, there is an excessive consumption of animal fats and easily digestible carbohydrates.
Keywords: biological value; ice cream; milk whey; milk proteins; кафедра технології молока і молочних продуктів; біологічна цінність; молочна сироватка; морозиво; молочні білки